BLOCKCHAIN FRAMEWORK FOR MEDICAL HEALTHCARE RECORDS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electronic health records (EHR) are the digital version of a patient’s medical paper chart. EHRs are patient-centered records that make information available instantly and these are secure and can be accessed only by authorized users. A patient stricken by a heavy medical condition needs to maintain the long history of the treatment method and post-treatment rehabilitation. Storing and sharing knowledge between multiple entities and maintaining access solely complicate the method of a patient’s treatment. This paper introduces a record storage system by implementing blockchain technology to store the data that helps to realize integrity and security. By incorporating medical records in a blockchain, genuineness and rigidity of records will be typically maintained; that put together helps to remain the data safe from third parties. Our system presents ways in which the authority can maintain the medical records with efficiency. Authorities like hospital management and patients can be authorized to add and access the information within the medical records.